Tunable rectification in a molecular heterojunction with two-dimensional semiconductors - Jaeho Shin (Nature Portfolio, 2020)
Molecular electronics holds promise for device miniaturization yet can only be realized by choosing specially designed molecular species to date. Here, Shin et al. show tunable rectifying characteristics in a molecular heterojunction with non-functionalized molecules and two-dimensional semiconductors.